Application of TOPSIS Method for Multi-Criteria Decision Making for Poultry Fields by Using GIS in Hilla District - Enas abid Alhafidh mohamme, Rawaa Salh Al-Saffar, Suhad Ahmed Ahmed (Mathematical Statistician and Engineering Applications, 2022)
Statistical methods and statistical decisions making were used to arrange and analyze. the primary data to get norms which are used with Geographic Information Systems (GIS) and spatial analysis programs to identify, the animals production and poultry units in strategic nutrition channels, also the priorities of food insecurity through the local production and import when there is no capacity for production. The poultry production is one of the most important commodities that satisfy human body protein requirements, also the most important criteria to measure the development and prosperity of nations. The poultry fields of Babylon Governorate are located in Abi Ghareg and Al_Kifil centers according to many criteria or factors such as the population, production ratio, rivers, distance between fields and streets, and the field’s spaces which identify by using TOPSIS method and GIS.TOPSIS and GIS are used to analyze the factors and limiting them to the main factor to know the most important influential factor. These factors consist of the natural and human changes which affect the actual ability to identify the defects according to statistical methods such as the nearest neighbor, the standard distance to build educational data bases aimed to facilitate the information exchange and analysis. The output data of TOPSISdivided into (supreme importance, most important, important, and less important)